North America. (1854)
Map shows major cities and physical features in Greenland, Russian America, British America, the United States, Mexico, the West Indies, and Central America; Nebraska, Minnesota, Kansas, New Mexico, Utah, Oregon, and Washington as western U.S. territories, plus "Indian territory." Relief shown by hachures. Scale [ca. 1:21,300,000].